Political Dynamics Behind the Discrepancies in Poland’s Refugee Acceptance Policy towards Refugees from Ukraine and Africa and the Middle East - Numadi, Katong Ragawi (Universitas Cenderawasih, 2023)
Poland hosts the most Ukrainian refugees as a result of Russian-Ukraine war. This reception clearly contradicts its closed-door policy, especially refugees from Africa and the Middle East. This article seeks to explain this contradiction. Using qualitative method by examining secondary sources, result shows that there are significant differences in Polish refuge policy concerning the recent Russo-Ukrainian War and the previous European refugee crises. Those differences are mainly driven by domestic and international politics. In the domestic realm, the rejection of refugees from the Middle East and North Africa is closely linked to the public negative sentiment and the rise of conservative political groups against those groups. In contrast, there is a large support of Polish political elements and public solidarity for Ukrainian refugees. Meanwhile, in the international realm, Poland’s activeness in accepting a significant number of Ukrainian refugees can be understood as a manifestation of Polish concern and resistance to the aggressiveness of Russian expansionism. KEYWORDS Political Dynamic; Poland; Refugee; Ukraine